The Role of Potassium and KUP/KT/HAK Transporters in Regulating Strawberry (Fragaria × ananassa Duch.) Fruit Development - José A. Mercado-Hornos; Claudia Rodríguez-Hiraldo; Consuelo Guerrero; Sara Posé; Antonio J. Matas; Lourdes Rubio; José A. Mercado (Plants)
Potassium is the most abundant macronutrient in plants, participating in essential physiological processes such as turgor maintenance. A reduction in cell turgor is a hallmark of the ripening process associated with fruit softening. The dynamic of K+ fluxes in fleshy fruits is largely unknown; however, the reallocation of K+ into the apoplast has been proposed as a contributing factor to the decrease in fruit turgor, contributing to fruit softening. High-affinity K+ transporters belonging to the KUP/HT/HAK transporter family have been implicated in this process in some fruits. In this study, a comprehensive genome-wide analysis of the KUP/KT/HAK family of high-affinity K+ transporters in strawberry (Fragaria × ananassa Duch.) was conducted, identifying 60 putative transporter genes. The chromosomal distribution of the FaKUP gene family and phylogenetic relationship and structure of predicted proteins were thoroughly examined. Transcriptomic profiling revealed the expression of 19 FaKUP genes within the fruit receptacle, with a predominant downregulation observed during ripening, particularly in FaKUP14, 24 and 47. This pattern suggests their functional relevance in early fruit development and turgor maintenance. Mineral composition analyses confirmed that K+ is the most abundant macronutrient in strawberry fruits, exhibiting a slight decrease as ripening progressed. Membrane potential (Em) and diffusion potentials (ED) at increasing external K+ concentrations were measured by electrophysiology in parenchymal cells of green and white fruits. The results obtained suggest a significant diminution in cytosolic K+ levels in white compared to green fruits. Furthermore, the slope of change in ED at increasing external K+ concentration indicated a lower K+ permeability of the plasma membrane in white fruits, aligning with transcriptomic data. This study provides critical insights into the regulatory mechanisms of K+ transport during strawberry ripening and identifies potential targets for genetic modifications aimed at enhancing fruit firmness and shelf life.